Estudio de prefactibilidad para el montaje del departamento de construcción de proyectos inmobiliarios vis y mayor a vis para la empresa Shagen ingeniería en Bogotá D.C (2017)
Analysis of prefactibility that allows to establish the feasibility and development of factibility for the mount of a department of construction of vis and major housing to vis in the company Shagen Ingenieria S.A.S